PROBLEMATICS OF SETTLEMENT OF INHERITANCE RIGHTS OF DAUGHTER WITH SIBLINGS IN THE MAHKAMAH SYAR’IYAH BANDA ACEH AND ACEH - Amri, Aulil (Universitas Islam Negeri Ar-Raniry, 2023)
This research discusses the Polarization of Judges' Decisions in the Settlement of Sibling Inheritance Rights (Case Study of Decision Number: 193/Pdt.G/2020/MS.Bna AND 21/Pdt.G/2021/MS.Aceh). The formulation of the problem studied is: 1. Why is there a disparity in the judge's decision regarding the position of relatives as heirs in an inheritance dispute at the Religious Court in decision number: 193/Pdt.G/2020/MS.Bna vs. 21/Pdt.G/2021/ MS. Aceh? 2. Has the judge's decision in resolving the dispute over the determination of heirs protected the rights of heirs in accordance with faraidh? This research is normative and practical juridical research, namely library research supported by results in the field in the form of interviews with related functional officials of the Banda Aceh Syar'iyah Court and Aceh Syar'iyah Court. This study concludes that: 1. The disparity in the decisions of the Banda Aceh Syar'iyah Court and the Aceh Syar'iyah Court occurred due to an understanding of the Jumhur Ulama's opinion which stated that a daughter cannot be hindered by a daughter in receiving an inheritance. Jumhur Ulama's definition of